TIPOLOGI FACADE BANGUNAN DAN PERKEMBANGAN ARSITEKTUR KOLONIAL Dl SANGA·SANGA, KABUPATEN KUTAI KARTANEGARA* - Oktrivia, Ulce (Naditira Widya, 2009)
Sanga Sanga is a city which was developed based on the growth of oil mining activities during the Dutch colonization in the east coast of Kalimantan. Archaeological researches indicated that Sanga Sanga was established as the centre of oil mining in the territory of the Sultanate of Kutai Kartanegara; other oil mining sites are Sanga Sanga, Angana, Semboja, Muara Badak, and Balikpapan. Being the centre of an oil mining activity, a number of mining facility were established such as housing, offices, storages, and public buildings. My observation suggests that each building indicate specific characteristics such as the fagade. This article discusses the typology of fagade in regard to the development of colonial architecture in Sanga Sanga.